Growth-site Quality Assessment of Nypa fruticans using Unmanned Aerial Vehicles Images: A case study in Kubu Raya Regency, West Kalimantan Province - Adelia Juli Kardika; I Nengah Surati Jaya; Nining Puspaningsih; Fairus Mulia (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The growth-site quality is one of the essential information needed to support sustainable forest management particularly in forestry planning. This paper describes the development of a site-quality class of Nypa vegetation by considering the biological and physical factors. The main objective of this study is to develop a discriminant model and to find out major factors that may be used to predict the quality of Nypa growth-sites.The model was developed using variables either measured on UAV images or from field measurement, namely soil texture (X1), water salinity (X2), water pH (X3), crown closure (X4) and stand density (N) measured on the UAV image (X5). The study found that the site quality of Nypa could be indicated by the variation of its biomass content. Then, it was concluded that the major factors that affect the site quality are the soil texture (X1),water salinity (X2),and water pH (X3) with 78.3% of overall accuracy.